2020
DOI: 10.5933/jkapd.2020.47.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Application of Teeth Whitening LED for Prevention of Dental Caries : Antimicrobial Photodynamic Therapy Approach

Abstract: The present study is aimed to assess the effect of antimicrobial photodynamic therapy (aPDT) on Streptococcus mutans biofilm through teeth whitening light emitting diode (LED).Planktonic and dynamic biofilm state cultures of S. mutans were used. Erythrosine 20 μM/L was used as the photosensitizer. Irradiation was performed by exposing cultures to clinic and homecare whitening LEDs for 15 minutes. The viability was measured through Colony Forming Unit counts and confocal laser scanning microscopy.aPDT using whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…The CFU counts immediately after treatment were significantly lower in Group II (PDT) than in Group I (negative control), thus verifying the antimicrobial ability of erythrosinemediated PDT on S. mutans. This is consistent with the results of previous studies [9,[11][12][13][14][15]. The American Society of Microbiology defines antimicrobial activity as a ≥3 log CFU/mL reduction from the starting inoculum [16].…”
Section: ⅳ Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The CFU counts immediately after treatment were significantly lower in Group II (PDT) than in Group I (negative control), thus verifying the antimicrobial ability of erythrosinemediated PDT on S. mutans. This is consistent with the results of previous studies [9,[11][12][13][14][15]. The American Society of Microbiology defines antimicrobial activity as a ≥3 log CFU/mL reduction from the starting inoculum [16].…”
Section: ⅳ Discussionsupporting
confidence: 91%
“…Studies have reported the use of erythrosine as a photosensitizer in PDT to exert antimicrobial effects against S. mutans cells in suspensions or biofilms [9,[11][12][13][14][15]. After antimicrobial treatment, residual bacteria induce the recovery of biofilm growth and CFU counts, indicating the possibility of reinfection.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDT group demonstrated a significantly reduced number of S. mutans microorganisms compared to the control and EDTA groups. This result supports the effectiveness of PDT against cariogenic bacteria, consistent with prior research [15][16][17]32,33]. However, PDT is less effective when dealing with mature biofilm state.…”
Section: A B C Dsupporting
confidence: 91%
“…It reduces the growth of Streptococcus mutans which ultimately prevents dental caries. This treatment will allow full arch irradiation 24 .…”
Section: Prevention Of Dental Cariesmentioning
confidence: 99%